Helping elementary preservice teachers learn to use curriculum materials for effective science teaching - Schwarz, Christina V.; Gunckel, Kristin L.; Smith, Ed L.; Covitt, Beth A.; Bae, Minjung; Enfield, Mark; Tsurusaki, Blakely K. (Science Education, 2008)
Curriculum analysis, modification, and enactment are core components of teacher practice. Beginning teachers rely heavily on curriculum materials that are often of poor quality to guide their practice. As a result, we argue that preservice teachers need to learn how to use curriculum materials for effective teaching. To address this concern, the authors conducted a study in which three teacher educators taught elementary science methods courses incorporating a major focus on curriculum analysis and modification based on Project 2061 Instructional Analysis Criteria. Analysis of pre–post assessments, classroom artifacts, classroom dialogue, and postcourse interviews indicated that preservice teachers accurately applied and appropriated a modest set of criteria whose intended meanings most closely matched their own understandings, were most closely aligned with their own goals and criteria, or were made accessible through systematic use and attention within the methods sections. However, many did not find the materials analysis criteria useful or comprehensible and based their curricular decisions on their own criteria. Furthermore, some preservice teachers resisted engaging in these practices that may have seemed too analytical, inauthentic, and destabilizing. These findings pointed us toward a revised theoretical framework and new approaches to better support preservice teachers' effective participation with curriculum materials. © 2008 Wiley Periodicals, Inc. Sci Ed92:345–377, 2008
Keywords: AIDS & devices; CURRICULUM evaluation; EDUCATION – Research; EDUCATIONAL quality; EDUCATIONAL resources; LESSON planning; OBSOLESCENCE of books; periodicals; etc.; Pedagogical Content Knowledge; SCIENCE – Study & teaching (Elementary); STUDENT teachers; TEACHER effectiveness; TEACHING aids & devices – Evaluation; Teaching Methods; research